2019
DOI: 10.1097/mpg.0000000000002480
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C19 and STAT6 Variants Influence the Outcome of Proton Pump Inhibitor Therapy in Pediatric Eosinophilic Esophagitis

Abstract: Objective: Proton pump inhibitors (PPIs) are an effective treatment for eosinophilic esophagitis (EoE); however, only 30% to 60% of patients respond. Common genetic variants in CYP2C19 and STAT6 associate with PPI plasma concentration and magnitude of inflammatory response, respectively. Our objective was to determine if genetic variation in the genes for CYP2C19 and STAT6 influence differentiation between PPI responsive esophageal eosinophilia versus PPI nonresponsive EoE (PPI-REE, PPI-nonresponsive EoE). Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 51 publications
1
25
1
2
Order By: Relevance
“…Notably, it was previously found that diets rich in fat significantly suppress natural killer T (NKT) cell-derived IFNγ production, but significantly enhance the production of IL-13, which activates carcinogenesis in NASH [45]. Another possible explanation for our finding of STAT6 association with HCC development in NASH was supported by a recent study, which showed that variant of STAT6 rs167769 is strongly associated with eosinophilic esophagitis [46]. Interestingly, it was confirmed recently that progression of NASH was significantly associated with increasing eosinophilic type 2 liver inflammation in experimental, as well as in human patient biopsies [6].…”
Section: Discussionsupporting
confidence: 58%
“…Notably, it was previously found that diets rich in fat significantly suppress natural killer T (NKT) cell-derived IFNγ production, but significantly enhance the production of IL-13, which activates carcinogenesis in NASH [45]. Another possible explanation for our finding of STAT6 association with HCC development in NASH was supported by a recent study, which showed that variant of STAT6 rs167769 is strongly associated with eosinophilic esophagitis [46]. Interestingly, it was confirmed recently that progression of NASH was significantly associated with increasing eosinophilic type 2 liver inflammation in experimental, as well as in human patient biopsies [6].…”
Section: Discussionsupporting
confidence: 58%
“…EREFS at the beginning of the high-dose PPI therapy period did not predict response to maintenance therapy. From BLRM, we found that patients who scored 5 or fewer eos/hpf after the initial 8 weeks of high-dose PPI therapy were greater than 3-fold more likely to remain in remission during maintenance therapy than individuals who initially scored fewer than 15 We previously reported that carriage of STAT6 variants rs324011, rs167769 and rs12368672 was associated with an increased eosinophil count in the distal esophagus, relative to noncarriers, on biopsy samples obtained before initiating PPI therapy, 14 while carriage of STAT6 variant rs1059513 was associated with decreased eosinophil counts in the distal esophagus. Therefore, we analyzed this group of SNPs for association with outcome of PPI maintenance therapy.…”
Section: Resultsmentioning
confidence: 99%
“…17 The CYP2C19 single-nucleotide polymorphisms (SNPs) investigated and assays used were as previously described. 14,17 The STAT6 SNPs investigated and the TaqMan assays used (Applied Biosystems, Waltham, MA) were as follows: rs1059513 (C___7480847_10), rs324011 (C____620399_10), rs167769 (C____620401_20), and rs12368672 (C__31186828_10). Genotype counts, SNP frequencies, and Hardy-Weinberg equilibrium P values are shown in Supplementary Table 1.…”
Section: Genotypingmentioning
confidence: 99%
“…Evidence linking CYP2C19 genotype-predicted phenotype and PPI adverse events in young children (0-3 years) as well as PPI responsiveness suggests the relevance of this PGx relationship in the pediatric population. 28,29 A recent simulation study linked CYP2C19 genotype-predicted phenotype with altered systemic exposure of the selective serotonin reuptake inhibitors, es/ citalopram and sertraline, in children and adolescents. Dose modifications based on genotype-predicted phenotype (i.e., PGx variation) were suggested, but this has yet to be evaluated prospectively.…”
Section: Communicating Testing Results To Pediatric Age Patients and mentioning
confidence: 99%